Evaluation of alexithymia in patients affected by rheumatoid arthritis and psoriatic arthritis: A cross-sectional study. Issue 4 (January 2019) - Chimenti, Maria Sole; Fonti, Giulia Lavinia; Conigliaro, Paola; Hitaj, Juna; Triggianese, Paola; Teoli, Miriam; Galluzzo, Marco; Talamonti, Marina; Kroegler, Barbara; Greco, Elisabetta; Perricone, Roberto
Abstract : Abstract: Rheumatoid arthritis (RA) and psoriatic arthritis (PsA) are chronic autoimmune diseases leading to joint damage, functional limitation, and disability and are typically associated with several comorbidities. Alexithymia is a personality trait characterized by a disregulation of emotion processing and regulation of emotions that involves a dissociation of emotional and physical responses to life events. A broad association between alexithymia and symptoms as depression, inflammation, and pain has been demonstrated. We aimed at evaluate an association among inflammatory arthritis, as RA and PsA, and alexithymia, and a possible link with clinical characteristics and disease activity. In this cross-sectional study, we enrolled, from January to December 2017, patients affected by RA or PsA referring to the outpatient's clinic of the Rheumatology Unit of the University of Rome Tor Vergata. The 20-item Toronto Alexithymia Scale (TAS-20) was used to assess alexithymia. Disease activity, function, quality of life, and clinimetric indexes were assessed. A total of 50 RA patients and 51 PsA patients were enrolled. The TAS-20 score showed 38.6% (39/101) patients had alexithymia, 26.7% (27/101) patients were in the borderline of alexithymia and 34.7% (35/101) patients did not have alexithymia. A statistical significant association was observed between alexithymia and inflammatory indices (ESR: P = .029, CRP: P = .043) and between alexithymia and clinimetric parameters (ptVAS, pVAS, GH, P < .0001 for all comparisons). A significant trend of association has been demonstrated between alexithymia and female gender and concomitant steroid therapy. No correlations among variables such as age, duration of disease, and comorbidities and alexithymia status were observed. This study suggests that alexithymia assessment should be a part of the comprehensive management of RA and PsA patients.